Trophic niche expansion during the non‑breeding season in kelp gulls of known breeding colony - Lisnizer, Nora (2018)
Year-round foraging strategies are key determinants of bird population dynamics. However, trophic ecology studies during the non-breeding period rarely focus on individuals from a known breeding colony, precluding links to demographic aspects of the target population or metapopulation. Using stable isotope analysis (δ15N, δ13C) of primary feathers moulted sequentially after breeding, we tested the trophic niche variation during the non-breeding seasons 2010 and 2011 in Kelp Gulls Larus dominicanus from a colony in coastal Patagonia (43º04′S, 64º29′W), Argentina. Isotopic niche position changed gradually from late summer to late autumn/early winter due to a progressive depletion in δ15N. In addition, niche spread showed a progressive expansion in the same study period. This niche expansion was consistent with the observed differences in the among-individual variability in feeding ecology suggested by niche metrics, being lower during the end of breeding compared to the non-breeding period. Low δ13C values of some feathers suggest that this expansion may be in part driven by the utilization of non-marine food resources/habitats by some individuals.